The Role of Overreaction in Consumer Goods Industry Sector - Cosmetics & Home Supplies on the Indonesia Stock Exchange - Siti Komariah; Safruji Nurbastian (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
This study aims to see whether there is an overreaction effect on the company's stock price in the Consumer Goods Industry Sector - Cosmetics & Home Supplies which are listed in the period January 2019 - February 2022 on the Indonesia Stock Exchange. Sampling in this study was carried out using purposive sampling method. This method has the criteria that the shares are always listed in the research period. The researcher uses data analysis in the form of simple linear regression and to answer normality using the Central Limit Theorem which is to find out whether the data submitted is normal. This study proves empirically that overreaction has an influence on stock prices, so that in its implications for stock investment investors do not have adequate understanding and are easy to accept information that is not necessarily true.